2019
DOI: 10.5001/omj.2019.63
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy as a Method for Relieving Symptoms of Cervical Ectopy: A Randomized Clinical Trial

Abstract: Objectives Benign cervical ectopy (CE) may cause chronic or recurrent symptoms leading to women repeatedly being referred to gynecology clinics. We aimed to present a safe and effective method for relieving symptoms of CE. Methods This double-blind clinical trial was conducted among 164 women with CE who complained of persistent or recurrent symptoms of cervicitis in the last six months. Patient’s demographic data, medical history, symptoms, and vaginal examination resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Cryotherapy (cryosurgery) of the cervix is an effective treatment for symptomatic cervical ectropion ( 33 ). Other surgical techniques have been applied for ablation of the squamocolumnar junction.…”
Section: Discussionmentioning
confidence: 99%
“…Cryotherapy (cryosurgery) of the cervix is an effective treatment for symptomatic cervical ectropion ( 33 ). Other surgical techniques have been applied for ablation of the squamocolumnar junction.…”
Section: Discussionmentioning
confidence: 99%
“…4 In 2019, Agah et al reported that cryotherapy showed no remarkable side effects and was associated with more satisfaction (p<0.001). 31 Adefuye et al reported that 98.2% of 220 women believed that the procedure had been as they expected, and 95% said that they would recommend cryotherapy to other women. 21 Lewis et al found 100% satisfaction with cryotherapy among 22 women surveyed at their 3-month follow-up visit.…”
Section: Resultsmentioning
confidence: 96%
“…CO 2 cryotherapy involves freezing temperatures of -22 to -30 °C, which results in crystallization and evaporation of intracellular fluid and ultimately, destruction of cells at -85 °C. The procedure is performed until the formation of an ice ball is noted, which takes up to five minutes, most often with freeze-thaw cycle [11]. Following CO 2 cryotherapy, the patient had a once-daily Kushen gel vaginal suppository placed for two weeks.…”
Section: Groupingmentioning
confidence: 99%